O composto de marketing como estratégia de conhecimento e uso, aplicada a MPE: uma analise da confeitaria La Fatia, localizada em Manaus-AM - Moraes, Thayná Saldanha de (Brasil, 2024)
It is notable how much micro and small companies have been growing over the last few years, at the same time that companies are opening at the same speed as they are closing. And one of the main reasons that lead to the mortality of these companies is the lack of knowledge and application of administrative tools, such as the creation of a strategic marketing plan, the lack of use of the marketing mix (product, price, place and promotion) . This study has the general objective of: analyzing the use of the 4P's of marketing at the company La Fatia and specifically describing the concepts of marketing mix as a business success strategy, analyzing how the marketing mix is constituted, and proposing practical recommendations for the improving the application of the 4Ps of marketing after interpreting the SWOT analysis. This study adopts a methodology that is based on qualitative and bibliographical approaches to achieve its objectives. As for the procedures, this is a case study, in which data collection was carried out, interviews were used, which enabled the construction of the results and discussions chapter. It is concluded: that the objective of the work was achieved, as it was possible to analyze how La Fatia works with its compound, together with contributing to it through the knowledge acquired in the academy. This research also offered valuable insights into how other MSEs can strengthen their presence in the market. Collaboration between academia and the business sector was fundamental in providing not only theoretical contributions, but also practical solutions to the challenges faced by MSEs. Encouraging other companies to adopt similar approaches, adapting them to their specific realities to achieve success in a competitive environment.